(untitled) (The Review of Diabetic Studies, 2025)
Diabetes mellitus is strongly associated with an increased risk of silent cardiovascular complications, making timely ECG monitoring a critical component of long-term care. In family medicine settings, the effectiveness of ECG follow-up depends not only on clinical expertise but also on the operational systems that support patient flow, result management, and continuity of care. This narrative review synthesizes evidence demonstrating the essential contribution of medical secretaries to ECG coordination for diabetic patients. Their roles—spanning scheduling, documentation, communication, and structured follow-up—bridge gaps that commonly hinder diagnostic pathways in primary care. Findings indicate that when administrative and clinical functions are integrated, ECG screening becomes more timely, result interpretation improves, and patient adherence increases. Within the Saudi Arabian context, strengthening workflow systems and enhancing the administrative capacity of medical secretaries align with national goals for optimizing chronic disease management under Vision 2030. The review concludes that operational coordination is as crucial as clinical expertise in delivering safe, efficient, and proactive cardiovascular surveillance for diabetic patients.